Validating and developing TLC-based fingerprinting for Curcuma longa L. - Kartini Kartini; Yunita A. Andriani; Widho Priambodo; Nikmatul I.E. Jayani; Mochammad A. Hadiyat (GarVal Editorial Ltda., 2021)
Context: Curcuma longa (turmeric) is extensively cultivated as spices and herbal medicines in tropical and sub-tropical countries. Geographical origin is known to significantly determine the quality of the herbs used and, consequently, the safety and efficacy of their products. Aims: To validate and develop TLC-fingerprint combined with chemometrics to differentiate C. longa collected from various origins. Methods: Thin Layer Chromatography (TLC) was employed together with chemometric methods, i.e., Principal Component Analysis (PCA) and Cluster Analysis (CA), to evaluate the quality of C. longa rhizomes collected from nine origins in Indonesia. Results: Chloroform, dichloromethane, and ethanol (64:64:1) were a suitable mobile phase for C. longa. The method used met the requirements for a stable and precise TLC system. As analyzed by the chemometric techniques, the TLC-fingerprints could discriminate C. longa from various origins. The PCA score plot of the first two principal components (PCs) and CA clearly distinguished two clusters of simples. Conclusions: When combined with PCA and CA, TLC-fingerprinting can discern the rhizomes of C. longa sourcedfrom various locations. TLC-fingerprints that are analyzed with chemometrics can be used as an alternative marker-oriented method for evaluating the quality of C. longa.